Impact of processing modes and parameters of the working part of the instrument on the surface quality of flat parts during high-speed friction hardening - Dmyterko, Petro; Novitskyy, Yuriy; Gurey, Volodymyr (Видавництво Львівської політехніки, 2017)
Impact of processing modes and parameters of the working part of the tool-workpiece on the quality and surface precision of details during high-speed friction hardening of flat details is developed.
Keywords: surface precision; surface roughness; oscillation; precessional motion; high-speed friction